Learning Strategies at SMP Muhammadiyah Porong During Pandemic Covid 19 - Wilujeng Dwi Safitri (International Consortium of Education and Culture Research Studies, 2021)
The development of education today is influenced by the rapid progress of information and communication technology. One of the information technology that plays a role in the world of education is online learning. Online learning serves as a liaison between educators and students with an internet network that can be accessed anytime and anywhere. The online media used by the research subjects are various (WhatsApp, Google Classroom, Edmodo, Zoom). The purpose of this study is to determine the effectiveness and strategies in online learning. The obstacle to online learning in the COVID-19 pandemic is quotas. While face-to-face learning, students come to school. The time required for learning is 2-3 hours.